The Potential of Established Fitness Cut-off Points for Monitoring Women with Fibromyalgia: The al-Ándalus Project - Castro-Piñero, José; Aparicio, Virginia A.; Estévez-López, Fernando; Álvarez-Gallardo, Inmaculada C.; Borges-Cosic, Milkana; Soriano-Maldonado, Alberto; Delgado-Fernández, Manuel; Segura-Jiménez, Víctor (International Journal of Sports Medicine, 2017)
The aim of the present study was to determinate whether fitness cut-off points discriminate the severity of major fibromyalgia symptoms and health-related quality of life. Additionally, we investigated which American Colleague of Rheumatology (ACR) fibromyalgia criteria (1990 vs. modified 2010) better discriminate fibromyalgia symptomatology. A total of 488 women with fibromyalgia and 200 non-fibromyalgia (control) women participated. All participants underwent both the 1990 and the modified 2010 ACR preliminary criteria (hereinafter 1990c and m-2010c, respectively). We used fitness cut-off points (Senior Fitness Tests Battery plus handgrip strength test) to discriminate between presence and absence of fibromyalgia. Additionally, we employed several instruments to assess fibromyalgia symptoms. Fitness cut-off points discriminated between high and low levels of the main symptoms the disease in all age groups (P from <0.001 to 0.01). Overall, the arm-curl and the 30-s chair stand tests presented the highest effect sizes in all symptoms, reinforcing the inclusion of fitness testing as a complementary tool for fibromyalgia diagnosis and monitoring. Moreover, the effect size of the differences in symptoms between women with fibromyalgia and controls were overall larger using the m-2010c compared with the 1990c, except for the tender points count, reflecting better the polysymptomatic distress condition of fibromyalgia.
Keywords: fitness tests threshold; pain; fatigue; health-related quality of life; depression; anxiety and diagnosis criteria